A HMCuS@MnO2 nanocomplex responsive to multiple tumor environmental clues for photoacoustic/fluorescence/magnetic resonance trimodal imaging-guided and enhanced photothermal/photodynamic therapy. Issue 23 (4th June 2020) - Li, Qian; Ren, Junjie; Chen, Qiubing; Liu, Weiwei; Xu, Zhigang; Cao, Yang; Kang, Yuejun; Xue, Peng
Abstract : Surface functionalization of HMCuS NPs with MnO2 as a gatekeeper of encapsulated Ce6 for tumor microenvironment responsive and imaging-guided combination therapy. Abstract : Hollow mesoporous copper sulfide nanoparticles (HMCuS NPs) are advantageous for loading small-molecule therapeutic drugs coupled with photothermal ablation for synergistic tumor therapy. However, treatment efficacy mediated by HMCuS NPs is not always satisfactory owing to their insensitivity toward the tumor microenvironment (TME), and unpredictable drug leakage may also result in deleterious systemic toxicity. Here, a novel HMCuS@MnO2 -based core–shell nanoplatform was developed as a highly efficient TME modulator, which could alleviate tumor hypoxia, deplete the level of intracellular glutathione (GSH) and trigger the dissolution of Mn 2+ . Moreover, MnO2, in situ grown on the surface of HMCuS, may act as a gatekeeper by forming a stimulus-responsive plug within the mesoporous structure, which effectively prevented the premature release of encapsulated photosensitizer chlorin e6 (Ce6) and was responsive to the acidic TME for demand-based drug release. Under the condition of 660/808 nm dual-wavelength laser irradiation, hyperthermia-mediated photothermal therapy (PTT) and reactive oxygen species (ROS)-mediated photodynamic therapy (PDT) can be triggered for tumor eradication, which were further enhanced upon the modification of the TME. In the meantime, splendid photoacoustic (PA)/fluorescence (FL)/magnetic resonance (MR) imaging properties of HMCuS@MnO2 /Ce6 (CMC) NPs could enable the realization of more precise, reliable and on-demand combination therapy. In a word, this study illustrated a promising approach to strengthen the efficacy of HMCuS-based nanotherapeutics, which would definitely promote the further exploitation of smarter nanoplatforms for synergistic disease management.